Schedulling activity untuk meningkatkan aktivitas sehari-hari penderita skizofrenia - Muthia Maharani (Procedia : Studi Kasus dan Intervensi Psikologi, 2021)
People with schizophrenia bring up positive and negative symptoms, among these symptoms cause sufferers to have no interest in one particular activity. This study aims to increase the activity of people with schizophrenia. The assessment methods used are interviews, observation, Wechsler Adult Intelligence Scale (WAIS), Thematic Apperception Test (TAT), Graphics and Wartegg Test. To deal with these problems, Scheduling Activity Method isused. The results obtained are the subject’s activity in leisure time increases so that daydreaming and hallucinating activities are reduced.